High Accuracy Modeling of Permanent Magnet Synchronous Motors Using Finite Element Analysis - Hanaa Elsherbiny; Laszlo Szamel; Mohamed Kamal Ahmed; Mahmoud A. Elwany (Mathematics, 2022)
Permanent magnet synchronous machines (PMSMs) have garnered increasing interest because of their advantages such as high efficiency, high power density, wide speed range, and fast dynamics. They have been employed recently in several industrial applications including robotics and electric vehicles (EVs). However, PMSMs have highly nonlinear magnetic characteristics, especially interior PMSMs, due to the existence of reluctance torque. Nonlinearity complicates not only machine modeling but also control algorithms. An accurate machine model is the key aspect for the prediction of machine performance as well as the development of a high-performance control algorithm. Hence, this paper presents an accurate modelling method for PMSMs. The proposed model method is applicable for all PMSMs, even multiphase machines. This paper considers a fractional slot concentrated winding 12/10 interior PMSM (IPMSM) for this study to demonstrate the effect of magnetic saturation and special harmonics. The developed model considers accurately the magnetic saturation, mutual coupling, spatial harmonics, and iron loss effects. It utilizes finite element analysis (FEA) to estimate the precise magnetic characteristics of IPMSM. The finite element model is calibrated precisely using experimental measurements. The iron losses are estimated within the simulation model as d- and q-axes current components. The model accuracy is validated experimentally based on a 12/10 IPMSM prototype.